Saudi EFL Learners’ Attitude Towards Integration of Video-Podcasts In Listening Comprehension - Shahid, Shahid Hussain; Zuraina, Ali (Open Access Publishing Group, 2017)
The use of podcasts is growing in the instructions of listening comprehension. However, the success of computer technology generally depends on learners positive attitudes towards it. The present study explored attitudes of Saudi EFL undergraduates toward the use of video-podcasts integration in listening comprehension. Moreover, the study also examined students’ attitude from the perspective of the number of video-podcasts they received in their instructions. Samples included 90 English major male undergraduates divided into three groups. The three groups received five (5), ten (10) and 15 video-podcasts in their listening classes before they answered an attitude questionnaire. ANOVA results revealed that the students had positive attitudes towards the use of video-podcasts in listening. However, no significant difference was found between the attitudes of the three experimental groups who received varied number of video-podcasts in their instructions.